The Relationship Between Social Communication and Social Functioning in Pediatric TBI: A Pilot Study - Genova, Helen M.; Haight, Alison; Natsheh, Joman Y.; DeLuca, John; Lengenfelder, Jean (Frontiers in Neurology, 2019)
Objective: Social communication presents a significant difficulty for children with traumatic brain injury (TBI). Although several measures are used to examine social communication, there is no gold-standard assessment tool. The present pilot study examined the ability of the Social Communication Disorders Checklist (SCDC) to detect social communication difficulties in pediatric TBI. Further, we examined the relationship between social communication and social functioning as assessed by parental ratings of behavior and objective measures of social cognition. Methods: Sixteen children with pediatric TBI and 20 age, education and sex matched healthy controls (HCs) participated. All participants participated in a neuropsychological evaluation and parents filled out questionnaires. Parents rated their children’s social communication abilities using the SCDC, as well as the Behavior Assessment System for Children, Second Edition (BASC-2). The pediatric subjects completed a task of social cognition, specifically Theory of Mind (ToM). Results: The pediatric TBI group had significantly lower scores on the SCDC compared to the HCs (p=0.001). In the pediatric group, SCDC scores correlated significantly with scores on the BASC-2, as well as performance on the ToM task, indicating that children with lower parent-rated social communication abilities also had lower scores on the objective measure of social cognition. Conclusions: These data provide preliminary evidence that children with TBI have difficulties with social communication , as evidenced by lower scores on the SCDC , and that SCDC scores correlate with subjective and objective measures of social cognition and behavior in pediatric TBI.